KEMASUKAN ISLAM KE ARKIPELAGO MELAYU: Kajian Pemikiran Hamka dalam Sejarah Umat Islam - Ahmad Nabil Amir (Hadharah: Jurnal Keislaman dan Peradaban, 2023)
This paper discusses the emergence and spread of Islam in the Malay Archipelago as articulated and brought forth by Hamka in Sejarah Umat Islam. In his significant analysis of the history of Islam in Malay Archipelago, Hamka established the fact that Islam comes to this region in 7th CE from Arab, and refuted the claims that it was spread later in 13th CE from Gujerat. This was reinforced with significant historical facts that evidently pointed out that Islam had been established in the Malay world early in 7th CE. This paper will analyze Hamka’s thought on the early development of Islam in Malay Archipelago and compared it with the works of Syed Muhammad Naquib al-Attas in Islam dalam Sejarah dan Kebudayaan Melayu (Islam in Malay History and Culture) that concluded the same thesis.